Human rights, human dignity, and cosmopolitan ideals essays on critical theory and human rights - Lutz-Bachmann, Matthias; Nascimento, Amos (Rethinking political and international theory, 2014)
This book proposes a new agenda for research into a Critical Theory of Human Rights. Each chapter pursues three goals: to reconstruct modern philosophical theories that have contributed to our views on human rights; to highlight the importance of humanity and human dignity as a complementary dimension to liberal rights; and, finally.